Apontamentos para uma definição comportamentalista de cultura - Fernandes, Diego Mansano [UNESP]; Carrara, Kester [UNESP]; Zilio, Diego (My University, 2017)
Behavioral analysis of social and cultural processes are not new in our field, since those were an important aspect of Skinner early interests, and a substantial part of his later works. However, the last three decades gave rise to new approaches to social and cultural processes, and this body of knowledge has been growing through theoretical, experimental and quasi-experimental research over the years. Although the field produced important innovations, one question remains particularly difficult to answer: the very definition of culture. Skinner made some observations on this subject, and more recently other researchers tried to discuss the matter and provide solutions, but different uses for the same word or the use of different words meaning the same thing poses a challenge to conceptual clarity. By means of a conceptual analysis of the works of Skinner, we aim to give a systematic position of Skinner's uses of the term culture. We found two main possibilities: 1) the use of the term culture as another way to say a set of contingencies; 2) the use of the term culture as another way to say a set of cultural practices. We discuss the theoretical implications of these possibilities, and ultimately argue, with further clarifications, for the definition of culture as a set of social contingencies. In doing so, we hope to provide a possible and coherent radical behaviorist definition of culture, which might serve as a guiding concept for further research in Behavioral Analysis of Culture.
Notes towards a behaviorist definition of culture
Keywords: Behavior analysis of culture; Conceptual research; Culture; Radical behaviorism